2016
DOI: 10.3390/ijms17101675
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization and Expression Analysis of the Solute Carrier 6 Gene Family in Silkworm (Bombyx mori)

Abstract: The solute carrier 6 (SLC6) gene family, initially known as the neurotransmitter transporters, plays vital roles in the regulation of neurotransmitter signaling, nutrient absorption and motor behavior. In this study, a total of 16 candidate genes were identified as SLC6 family gene homologs in the silkworm (Bombyx mori) genome. Spatio-temporal expression patterns of silkworm SLC6 gene transcripts indicated that these genes were highly and specifically expressed in midgut, brain and gonads; moreover, these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Generally, glycine transporters include two isoforms (GlyT1 and GlyT2), and their tissue distributions are quite different (Aroeira et al, 2014). In silkworm, three glycine transporters have been identified, which are named BmGT1, BmGT2 and BmGT1-L. BmGT1-L transcripts are specifically expressed in the midgut of larvae (Tang et al, 2016). Immunofluorescence results uncovered that BmGT1-L was solely…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, glycine transporters include two isoforms (GlyT1 and GlyT2), and their tissue distributions are quite different (Aroeira et al, 2014). In silkworm, three glycine transporters have been identified, which are named BmGT1, BmGT2 and BmGT1-L. BmGT1-L transcripts are specifically expressed in the midgut of larvae (Tang et al, 2016). Immunofluorescence results uncovered that BmGT1-L was solely…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila melanogaster (Dm), Ntl is similar to human GlyT2 and is required for Drosophila spermiogenesis (Chatterjee et al, 2011). In addition, a previous study has identified three GlyTs in the silkworm genome, which were named BmGT1, BmGT2 and BmGT1-L (Tang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first identification and cloning of γ-aminobutyric acid transporters in humans in 1990 [19], an increasing number of AAAP transporters has been recognized in a series of insect species, including Drosophila melanogaster [20,21], Bombyx mori [22], Bemisia tabaci [23], Leptinotarsa decemlineata [24], and several hemipterans belonging to Phylloxeridae [25]. Rapidly developing next-generation sequencing technology and bioinformatics algorithms are useful tools for identifying the AAAP transporters at a genome-wide level.…”
Section: Introductionmentioning
confidence: 99%